2014
DOI: 10.1016/j.jcrs.2013.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Binocular function in patients with pseudophakic monovision

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Traditionally, monovision is induced in the non-dominant eye, thereby correcting it for near vision, whereas the dominant eye remains corrected for distant vision. [5] Iatrogenic anisometropia may occur after any intraocular operations. As mentioned above, anisometropia may affect stereopsis but the problem is that there was no gold standard stereotest, and stereoacuity results would be affected by the measurement method.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, monovision is induced in the non-dominant eye, thereby correcting it for near vision, whereas the dominant eye remains corrected for distant vision. [5] Iatrogenic anisometropia may occur after any intraocular operations. As mentioned above, anisometropia may affect stereopsis but the problem is that there was no gold standard stereotest, and stereoacuity results would be affected by the measurement method.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that IOLs implanted bilaterally using the mini-monovision approach result in few optical side effects and exceptional distance and intermediate visual outcomes. Concerns remain regarding near visual outcomes that require some patients to wear spectacles for reading fine print or computer work [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ito et al. () pointed out the possibility of problems occurring after monovision surgery due to changes in ocular deviation and stereopsis in pseudophakic patients with near exophoria higher than 10 Δ. Supporting the idea that monovision induction in patients with preoperative moderate‐to‐high exophoria should be considered with utmost care, Ito reported cases of intermittent exotropia two years after monovision surgery in pseudophakic patients with preoperative near exophoria higher than 12 Δ (Ito et al.…”
Section: Resultsmentioning
confidence: 99%